Characteristics of ground level ozone and Nitrogen Dioxide concentrations during critical transformation time in urban area - Khong, Wai Wei (2018)
Ground level ozone (O3) is a secondary pollutant, which is formed from the photochemical reaction between NOX and VOCs. 1t has been highlighted as the most pervasive global air pollutant due to its adverse effect on human health and crop yields. The prior aim of the study is to investigate the characteristic of O3 from its precursor, nitrogen dioxide (N02), during critical transformation time (CCT) in the urban area. The datasets of three selected urban area from 2013 to 2014 were obtained from Department of Environment (DOE), which were then undergo multivariate analysis. The mean O3 concentration recorded throughout 2013 and 2014 in Kota Bharu (KB), Putrajaya (PJ) and Shah Alam (SA) is 15.56 ppb, 21.34 ppb and 19.17 ppb, respectively. Meanwhile, the mean O3 concentration during CCT is 13.07 ppb, 13.51 ppb and 12.14 ppb, respectively. The box and whisker plot showed that the data of O3 and NO; concentration in 2013 and 2014 are skewed to the right. It has been found that the O3 concentration is high staning from March to May due to Southwest monsoon season in PJ and SA. However, O3 concentration in KB is recorded to be the highest starting approximately from May 2013, while in 2014, the O3 concentration is high starting from January to February, then from April to August. Critical conversion point (CCP) was observed to be occurring within the CCT, from 8.00 a.m. to 11.00 a.m., using the diurnal plot and the O3 maxima were observed, usually after CCT at approximately 2.00 p.m. to 4.00 p.m. A model was developed by using multiple linear regressions (MLR) to ﬁt the observed data obtained from monitoring sites. A relatively low R2 value (005426) is obtained from the scatter plot, which indicates that the O3 concentration is difﬁcult to be predicted in atmospheric studies.